Peran bapa dalam keluarga di Gereja Kristen Sangkakala Indonesia jemaat Genesaret - Zakharia Suparyadi; Faozanolo Zebua; Mulyani Susana; Penni Ani Simanungkalit; Mihardo Saputro (Davar : Jurnal Teologi, 2025)
ABSTRACTThe father's role in the family is a fundamental factor in shaping the family's quality, both socially, psychologically, and spiritually. However, the weakening of the father's role—often reduced to merely a breadwinner—presents a serious challenge in contemporary family life, including within the church. This study aims to empirically examine the level of understanding and implementation of the father's role in Christian families, as viewed from nine role indicators: head of the family, breadwinner, protector, role model, educator, intermediary (priest), teacher, prophet, and king. The study used a quantitative approach with a survey method of 44 respondents from the congregation of the Indonesian Sangkakala Christian Church, Gennesaret Congregation. The research instrument underwent validity and reliability tests, demonstrating valid and reliable results. The results indicate that all indicators of the father's role have a strong to very strong relationship with each other, with the role of intermediary (priest) possessing the highest influence. These findings confirm that the father's spiritual role is the primary foundation that strengthens other roles in the Christian family. This research makes an empirical contribution to the development of family theology and the practice of fathering in the church.Keywords: Role of father, Family quality, Christian family, Priest. ABSTRAKPeran bapa dalam keluarga merupakan faktor fundamental dalam pembentukan kualitas keluarga, baik secara sosial, psikologis, maupun spiritual. Namun, fenomena melemahnya fungsi ayah—yang kerap direduksi hanya sebagai pencari nafkah—menjadi tantangan serius dalam kehidupan keluarga masa kini, termasuk di lingkungan gereja. Penelitian ini bertujuan untuk mengkaji secara empiris tingkat pemahaman dan pelaksanaan peran bapa dalam keluarga Kristen, ditinjau dari sembilan indikator peran, yaitu sebagai kepala keluarga, pencari nafkah, pengayom, pemberi teladan, pendidik, perantara (imam), pengajar, nabi, dan raja. Penelitian menggunakan pendekatan kuantitatif dengan metode survei terhadap 44 responden jemaat Gereja Kristen Sangkakala Indonesia Jemaat Genesaret. Instrumen penelitian telah melalui uji validitas dan reliabilitas yang menunjukkan hasil valid dan reliabel. Hasil penelitian menunjukkan bahwa seluruh indikator peran bapa memiliki hubungan yang kuat hingga sangat kuat satu sama lain, dengan peran sebagai perantara (imam) menempati pengaruh tertinggi. Temuan ini menegaskan bahwa peran rohani bapa merupakan fondasi utama yang memperkuat peran-peran lainnya dalam keluarga Kristen. Penelitian ini memberikan kontribusi empiris bagi pengembangan teologi keluarga dan praktik pembinaan kaum bapa di gereja.Kata kunci: Peran bapa, Kualitas keluarga, Keluarga Kristen, Imam.